2010
DOI: 10.1001/archgenpsychiatry.2010.9
|View full text |Cite
|
Sign up to set email alerts
|

Increased BDNF Promoter Methylation in the Wernicke Area of Suicide Subjects

Abstract: BDNF promoter/exon IV is frequently hypermethylated in the Wernicke area of the postmortem brain of suicide subjects irrespective of genome-wide methylation levels, indicating that a gene-specific increase in DNA methylation could cause or contribute to the downregulation of BDNF expression in suicide subjects. The reported data reveal a novel link between epigenetic alteration in the brain and suicidal behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
217
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(245 citation statements)
references
References 44 publications
14
217
1
5
Order By: Relevance
“…Further corroborating the involvement of these mechanisms in depression neurobiology, increased DNMT expression (23) and increased DNA methylation in specific genomic loci have been reported in the brain of depressed individuals (24)(25)(26)(27)(28). Moreover, our research group has recently shown that decreasing DNA methylation by means of pharmacological treatment with 5-AzaD, a DNMT inhibitor (DNMTi) induces antidepressant-like effects in different preclinical models (29).…”
Section: Introductionsupporting
confidence: 62%
“…Further corroborating the involvement of these mechanisms in depression neurobiology, increased DNMT expression (23) and increased DNA methylation in specific genomic loci have been reported in the brain of depressed individuals (24)(25)(26)(27)(28). Moreover, our research group has recently shown that decreasing DNA methylation by means of pharmacological treatment with 5-AzaD, a DNMT inhibitor (DNMTi) induces antidepressant-like effects in different preclinical models (29).…”
Section: Introductionsupporting
confidence: 62%
“…Although DNA methylation shows significant between-tissue variation, some interindividual differences in DNA methylation are correlated across brain and blood of healthy subjects (33), suggesting that epigenetic profiling of peripheral tissue may be useful for studies of brain disorders. Consistent with this hypothesis, DNA methylation changes have been found both in psychiatric postmortem brain samples (34,35) and in peripheral blood of the living psychiatric patients (12)(13)(14). However, a challenge to this field of study is whether epigenetic markers in peripheral tissues can predict functionally relevant epigenetic changes in the brain and consequent behavioral and psychiatric outcomes.…”
Section: Discussionmentioning
confidence: 80%
“…We focused our study on BDNF because it represents a particularly good candidate for early detection of psychiatric risk. BDNF has a well-established role in neurodevelopment and neuronal plasticity, and its deficiency has been linked to several psychiatric disorders that are associated with early-life adversity, including depression (34,36), schizophrenia (37), bipolar disorder (38), and autism (39). It seems likely that disrupted neural development and neural plasticity, associated with altered BDNF expression emerging in early life, could predispose an individual to behavioral deficits and multiple psychopathologies in adulthood (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study translating results from early developmental experiences in rodents, McGowan et al (2009) showed increased methylation at a homologous locus along the promoter of the glucocorticoid receptor in the post-mortem brains of human suicide victims who had experienced childhood abuse. Keller et al (2010) report increased promoter methylation of the BDNF IV promoter in suicide victims.…”
Section: Studies In Psychiatric Subjectsmentioning
confidence: 96%